2011
DOI: 10.1016/j.sedgeo.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Bloedite sedimentation in a seasonally dry saline lake (Salada Mediana, Spain)

Abstract: Salt crusts covering the surface of the Salada Mediana, a seasonally dry saline lake in northern Spain, consist predominantly of bloedite (Na 2 Mg(SO 4 ) 2 .4H 2 O). Microscopic features of the crust were investigated to understand processes of bloedite sedimentation. This study was combined with satellite and airborne observations, revealing asymmetrical concentric and parallel-linear patterns, related to wind action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Atmospheric conditions can also influence general reflectivity collected by this sort of imaging sensor, and so careful normalization of crust reflectance values was undertaken using a standard grey calibration tile (15 cm × 15 cm) that was placed within the camera field‐of‐view on the surface of the crust. Similar links to decreased reflectance in response to higher pore moisture, or from minerals with greater structural or absorbed water, have been made in larger scale remote sensing of sodic playas by Mees et al (). We therefore calculated mean DN values of 100 × 100 pixel squares in each IR image for (a) the calibration tile, (b) a ridged crust and (c) a continuous crust.…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…Atmospheric conditions can also influence general reflectivity collected by this sort of imaging sensor, and so careful normalization of crust reflectance values was undertaken using a standard grey calibration tile (15 cm × 15 cm) that was placed within the camera field‐of‐view on the surface of the crust. Similar links to decreased reflectance in response to higher pore moisture, or from minerals with greater structural or absorbed water, have been made in larger scale remote sensing of sodic playas by Mees et al (). We therefore calculated mean DN values of 100 × 100 pixel squares in each IR image for (a) the calibration tile, (b) a ridged crust and (c) a continuous crust.…”
Section: Methodssupporting
confidence: 58%
“…High diurnal temperature ranges mean that fluctuations in playa surface pore‐water concentration and chemistry are particularly significant both overnight and early in the morning (Kampf et al , ; Groeneveld et al , ). This general change in moisture availability at the sediment surface can be manifested either within the chemical structure of the evaporite minerals or as free water within the pores of the crust fabric (Mees et al ., ). On playa surfaces, moisture transfer can occur both above and below any apparent crust through evaporation, capillary transport (Rodriguez‐Navarro et al , ; Benavente et al , ; Genkinger and Putnis, ; Benavente et al , ; Grossi et al , ), and occasionally surface condensation (Kinsman, ; Thorburn et al , ).…”
Section: Introductionmentioning
confidence: 97%
“…Blödite [Na 2 Mg(SO 4 ) 2 •4H 2 O], P2 1 /a space group, a=11.1136(3) Å, b= 8.2421(3) Å, c = 5.5328(2) Å, β=100.873(3)º, V= 497,70(8) Å 3 , Z=2, is a common constituent of evaporitic sedimentary terrestrial environments (Garrett 2001;Mees et al 2011) consisting of parallel layers of MgO 2 (H 2 O) 4 and NaO 4 (H 2 O) 2 octahedra interconnected by SO 4 tetrahedra and hydrogen bonds (Figure 1;Rumanova 1958;Vizcayno and Garcia-Gonzales 1999). The occurrence of hydrated Mgand Na-mineral sulfates end members within extra-terrestrial planets have been previously reported (Nash and Fanale 1977;McCord et al 1999McCord et al , 2001Shirley et al 2010;Dalton et al 2012Dalton et al , 2012b, and considered as a potential carrier of water in our solar system that might result in the stability of numerous Mg-Na solid solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Mirabilite is regarded as a good indicator of cold/dry environments (Herrero et al, 2015; Zheng et al, 2000) and has proven to be very useful in the study of paleoclimate (Grasby et al, 2013; Herrero et al, 2015; Wang et al, 2012). Bloedite and gypsum have been found in various saline lakes in arid or semi-arid regions around the world and are used as indicators in paleoclimatology and sedimentology (Liu et al, 2008; Mees et al, 2011; Sönmez and Çelik, 2016). These minerals are generally related to intensive evaporation under warm/dry conditions (Escavy et al, 2012; Li et al, 2010; Sönmez and Çelik, 2016; Valero-Garcés et al, 2000).…”
Section: Discussionmentioning
confidence: 99%